American poetry now : Pitt poetry series anthology - Ochester, Ed (Pitt poetry series., 2007)
An anthology of poems by contemporary American authors, featuring works from Mark Cox, Billy Collins, Denise Duhamel, Etheridge Knight, Sandra Kohler, and other notable writers.